Status of post-lockdown mental well-being in Bangladeshi adults: A survey amidst COVID-19 pandemic - Mohammad Ali (Public Library of Science (PLoS), 2022)
Lockdown has been recognized as a gold standard measure to limit COVID-19 infection among the general population; however, it has a deleterious impact on their mental well-being. Many studies measured the mental well-being of different population groups during the lockdown period. Nonetheless, very little is known about the mental well-being of the general population when the lockdown has been relaxed or withdrawn in a particular country. Our study aimed to measure the mental well-being of the general population when the lockdown was lifted in Bangladesh. A cross-sectional survey was conducted from December 1, 2020, to February 28, 2021, using both web-based data collection and in-person interview facilities. Data from 3035 general Bangladeshi aged 18 and above were analyzed. Mental well-being was measured using the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) (Registration ID: 518226001). A multivariable linear regression model was employed to find the influential variables after controlling the confounders. The mean well-being score was 43.66. Well-being score was significantly lower among women (slope -2.171, p = <0.001), low-educated (slope -2.485, p = 0.018), and currently not working (slope -2.263, p = <0.001) population. However, we found significantly higher mental well-being scores among those with no comorbidity (slope 3.436, p = <0.001). Though the withdrawal of the lockdown improved the overall mental well-being of the general population, women, low-educated, not working, and the comorbid population were still suffering from low mental well-being problems. Special attention is recommended to address the vulnerable population when discussing the mental health of adult Bangladeshi during and after the COVID-19 pandemic.